Pengaruh Kualitas Makanan, Store Atmosphere terhadap Loyalitas Konsumen dengan Kepuasan Konsumen sebagai Variabel Intervening - Anang Kurniawan; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to test whether there is an influence on food quality, store atmosphere on consumer loyalty Mie Gacoan Yogyakarta by mediating by consumer satisfaction. The study used quantitative research methods with questionnaires as data collection techniques. The sample in this study amounted to 100 respondents taken using non probability sampling techniques with a type of sampling, namely purposive sampling. The data obtained is then analyzed using the outer model test, the inner model test and the hypothesis test (t test). The data analysis process is assisted by smart PLS 3 for windows applications. The results showed 1) Variables in food quality and store atmosphere each had a positive and significant effect on consumer satisfaction. 2) Consumer satisfaction variables have a positive effect on consumer loyalty. 3) Consumer satisfaction variables have a positive and significant effect on consumer loyalty. 4) Store atmosphere variables have no effect on consumer loyalty. 5) Food quality variables have a positive and significant effect on consumer loyalty with consumer satisfaction as an intervening variable. 6) Store atmosphere variables have a positive and significant effect on consumer loyalty with consumer satisfaction as intervening variable. Keywords: Food Quality; Store Atmosphere; Consumer Satisfaction; Consumer Loyalty; Mie Gacoan